TRANSITION FROM CONVENTIONAL TO VIRTUAL DENTAL IMPRESSIONS: A NARRATIVE REVIEW - Pochwalski, Jakub; Borek, Natalia; Gałązka, Julia; Miśkiewicz, Emilia; Krupa, Hanna; Stopa, Ewa; Wieczorek, Zofia; Kędrak, Magdalena; Stanisławski, Dominik; Jabłońska-Trzosek, Wiktoria (International Journal of Innovative Technologies in Social Science, 2026)
Digital impression systems have become an important development in prosthodontic and orthodontic practice, offering an alternative to conventional impression techniques. This narrative review examined the literature on the clinical performance, accuracy, workflow efficiency, and patient-centered outcomes of conventional and virtual impressions. Searches were conducted in PubMed/MEDLINE, Scopus, and Google Scholar using relevant terms related to intraoral scanners, digital impressions, conventional impressions, accuracy, trueness, precision, prosthodontics, and patient-reported outcomes. The literature suggests that digital impressions are a reliable option for many routine applications, particularly single-unit and short-span restorations, where they provide clinically acceptable accuracy and clear advantages in patient comfort and workflow efficiency. Reviews of patient-reported outcomes consistently show that patients generally prefer intraoral scanning because it is associated with less discomfort and more favorable experiences related to taste, smell, sound, vibration, nausea, and queasiness. Evidence from pediatric studies similarly indicates that children often prefer digital impressions and tolerate them better than conventional methods. However, the evidence is less consistent for full-arch and other technically demanding cases, in which cumulative scanning errors may reduce accuracy and conventional impressions may remain preferable. Overall, the findings support a selective rather than universal replacement of conventional techniques. Digital impressions appear best suited to cases in which efficiency, patient experience, and digital integration are priorities, while conventional methods continue to have value when maximal precision is essential.